EFFECT OF ISOTATIC REBOUND ON MODELLED ICE VOLUME VARIATIONS DURING THE LAST 200 KYR - Crucifix M.; Loutre M.-F.; Berger A.; Lambeck K. (My University, 2001)
Deformation of the lithosphere under an ice load can be approximated using the hypothesis of local damped isostasy. This simple formulation has been systematically compared with a three-dimensional model of the crust-mantle system for simple ice-load scenarios with a period in the range 20-100 kyr. The comparison enables us to introduce the concepts of effective upper mantle density and effective relaxation time into the isostatic model for the response of the Earth to the ice sheets. These parameters depend on the Earth model considered, ice sheet size and the period of the load cycle. The local damped isostasy model has been implemented in the Louvain-la-Neuve climate model to assess the impact of isostasy on continental ice volume variations for the last 200 kyr. Results suggest that isostasy acts as a negative feedback for ice volume during the glaciation process and acts as a positive feedback during the deglaciation. Moreover, taking isostasy into account is necessary to simulate variations in Northern Hemisphere ice volume during isotopic stage 3. Lastly, the use of effective mantle density and effective relaxation time improves the model performance regarding SPECMAP reconstructions.